Hubungan pH dan Nitrat Pada Air Parit Dengan Kejadian Penyakit Dermatitis Pada Pekerja di Perkebunan Kelapa Sawit - Siti Saadah; Syarifudin A.; Sulaiman Hamzani (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2019)
Abstract: Correlation Of pH and Nitrate On Ditch Water With The Incident Of Dermatitis Disease On Workers At Oil Palm Plantation. Water is closely related to health to prevent the occurrence of waterborne diseases, it must meet the health requirements that set in the standards of clean water quality, namely Minister of Health Regulation No. 416 / Menkes / PER / IX / 1990. With the aim to find out whether there is a relationship of pH and nitrates in the ditch water with the incidence of dermatitis disease on workers at oil palm plantations PT. Kharisma Inti Usaha 4 Kabupaten Tapin. Including pH